2009
DOI: 10.1016/j.triboint.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of pedestrian slip on flooring contaminated with solid particles

Abstract: Statistics by the UK Health and Safety Executive (HSE) suggest that slips, trips and falls account for up to one in three major workplace accidents. Many of these accidents are the result of contaminant (fluid or solid) within the shoe-floor contact.Though the lubrication mechanisms for liquid contaminants within the contact are well understood, the same cannot be said for particulate contaminants. This paper considers the key parameters controlling friction in a shoe-floor contact contaminated with various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 8 publications
(8 reference statements)
1
34
0
Order By: Relevance
“…Friction measurements on surfaces covered with sand particles was investigated by Li et al (2007). Mills, Dwyer-Joyce, and Loo-Morrey (2009) measured friction with various particulate contaminants of different diameters (calcite and silicon) and shape factors and floors with different roughness values. They reported that the adhesive friction is significantly affected by particulate contaminants while the hysteretic component is not.…”
Section: Tribologymentioning
confidence: 99%
“…Friction measurements on surfaces covered with sand particles was investigated by Li et al (2007). Mills, Dwyer-Joyce, and Loo-Morrey (2009) measured friction with various particulate contaminants of different diameters (calcite and silicon) and shape factors and floors with different roughness values. They reported that the adhesive friction is significantly affected by particulate contaminants while the hysteretic component is not.…”
Section: Tribologymentioning
confidence: 99%
“…The traction a particle-based surface, such as an artificial clay tennis surface, provides will increase with its shear strength. The shear strength of a surface with particle layers, such as an artificial clay tennis surface, will also be dependent on the normal load [27]. The normal loading conditions affect the cohesion between particles which will affect the surface's resistance to shear [28][29].…”
Section: Mechanical Shoe-surface Traction Test Devicesmentioning
confidence: 99%
“…Particles below 50 µm have been shown to form strong cohesive bonds in dry conditions [41]. It has been reported that below 50 μm particles do not act as individual entities and instead form layers with high inter-particle shear strength [27,41]. Under increased normal loading it is likely that the shear strength of the dry ACC1 surface will increase as particles are compressed and cohere.…”
Section: The Influence Of Normal Loading On the Initial Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Mills et al [12] and more recently Y. Hichri et al [13,14] have observed that friction is already reduced on dry contaminated roads. These authors measured the friction by means of a Skid Resistance Tester (SRT) Pendulum which is widely used on roads field as a reference.…”
Section: Introductionmentioning
confidence: 98%